2010
DOI: 10.1603/me10069
|View full text |Cite
|
Sign up to set email alerts
|

New Findings of Insecticide Resistance in Triatoma infestans (Heteroptera: Reduviidae) From the Gran Chaco

Abstract: Chagas disease is a major health concern in Latin America, and Triatoma infestans (Klug, 1834) is responsible for the majority of cases of Chagas disease in the continent. After the discovery of deltamethrin highly resistant populations in the neighboring areas to Yacuiba (Bolivia) and Salvador Mazza (Argentina), we studied T. infestans populations north and southward, with the aim of describing the range of the resistant area. In addition, tests were conducted to describe the susceptibility to fipronil in del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 17 publications
2
61
1
2
Order By: Relevance
“…Previous data showed that resistance of domestic T. infestans to deltamethrin is widespread, high in Argentina (Vassena & Picollo 2003, Audino et al 2004) and particularly high in Bolivia, where the highest levels of resistance were observed in the department of Tarija (Alarico et al 2010, Germano et al 2010, Lardeux et al 2010). The present results confirmed this tendency, with the highest RR observed in the domestic population of Taiguati (RR = 818), a colony of approximately 25 specimens collected in a henhouse.…”
Section: Discussionmentioning
confidence: 96%
“…Previous data showed that resistance of domestic T. infestans to deltamethrin is widespread, high in Argentina (Vassena & Picollo 2003, Audino et al 2004) and particularly high in Bolivia, where the highest levels of resistance were observed in the department of Tarija (Alarico et al 2010, Germano et al 2010, Lardeux et al 2010). The present results confirmed this tendency, with the highest RR observed in the domestic population of Taiguati (RR = 818), a colony of approximately 25 specimens collected in a henhouse.…”
Section: Discussionmentioning
confidence: 96%
“…2014), the emergence of insecticide resistance (Germano et al . 2010; Lardeux et al . 2010) and decentralized vector control initiatives in areas of recurrent political, social and economic instability (Gürtler 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that vector control failures, are due to high levels of insecticide resistance in this area [18][19][20][21]. In the last few years, more studies demonstrated that the phenomenon of resistance to insecticides in domestic T. infestans populations presents an extensive distribution in southern Bolivia and northern Argentina [21][22][23], with high resistance ratios, and different toxicological profiles [14,18,19,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%